Feasibility study: A Basic Income pilot project for Wales. A response to the report "Piloting a Basic Income in Wales" - Malcolm Torry (Albert-Ludwigs-Universität Freiburg, Freiburg Institute for Basic Income Studies (FRIBIS), 2021)
A Basic Income is an equal, regular and unconditional income for every individual of the same age. Following increasing political interest in the idea in Wales, in June 2021 the think tank Autonomy and the Basic Income Conversation (hosted by the think tank Compass) published Piloting a Basic Income in Wales: Principles, precedents and feasibility (Goodman et al., 2021). The report begins by responding to three questions: 'What is a Basic Income?', 'What are the potential advantages?', and 'What are Basic Income pilots?'. It then discusses 'The state of play in Wales', 'Progress at the UK level', 'Moving forward in Wales', 'Beginning with the "why"' (a study of the reasons for holding Basic Income pilot projects), and finally 'Pilot design: An option for Wales': a detailed proposal for a Welsh Basic Income pilot project. An appendix contains descriptions of previous experiments around the world.
Keywords: 330